2006
DOI: 10.1002/hyp.6050
|View full text |Cite
|
Sign up to set email alerts
|

Physically based modelling of sediment generation and transport under a large rainfall simulator

Abstract: Abstract:A series of large rainfall simulator experiments was conducted in 2002 and 2003 on a small plot located in an experimental catchment in the North Island of New Zealand. These experiments measured both runoff and sediment transport under carefully controlled conditions. A physically based hydrological modelling system (SHETRAN) was then applied to reproduce the observed hydrographs and sedigraphs. SHETRAN uses physically based equations to represent flow and sediment transport, and two erodibility coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 17 publications
0
19
1
Order By: Relevance
“…Wicks et al, 1992;Adams & Elliott, 2006). The soil erodibility coefficients k r and k f increase in value as the soil becomes easier to erode (i.e.…”
Section: Shetran Erosion and Sediment Yield Componentmentioning
confidence: 99%
See 1 more Smart Citation
“…Wicks et al, 1992;Adams & Elliott, 2006). The soil erodibility coefficients k r and k f increase in value as the soil becomes easier to erode (i.e.…”
Section: Shetran Erosion and Sediment Yield Componentmentioning
confidence: 99%
“…Thus Bathurst et al (1996) found that conductivities evaluated at the plot scale could be successfully applied with a model grid spacing of 2 km for the 701 km 2 Cobres basin in Portugal. Likewise Adams and Elliott (2006) calculated different coefficient values for the more and less erodible conditions of winter and summer respectively. However, for basins with hilly terrain, experience is that model conductivity values are relatively high compared with point measurements (e.g.…”
Section: Use Of Erosion Plots For Parameter Evaluationmentioning
confidence: 99%
“…Figure 1 shows ground elevations along a transect of the main channel of the Pukemanga Catchment and the locations of monitoring devices. A 1050 m 2 sub-area of the catchment was the subject of experimental studies of runoff processes under a large rainfall simulator (Adams et al, 2005;Adams and Elliott, 2006;Müller et al, 2006).…”
Section: Catchment Descriptionmentioning
confidence: 99%
“…The transport of suspended solids from storm runoff and their environmental impact has been widely discussed (Zonta et al 2005;Adams and Elliot 2006). However, little effort has been devoted to evaluating the contribution of the mineral composition of the actual soils to their settling behavior.…”
Section: Introductionmentioning
confidence: 99%